Assessment of Mangrove Replanting Failures in Tanjung Kepah From the Perspective of Environmental Factors - Shaharum, Syahmi Anas (Universiti Teknologi PETRONAS, 2021)
Mangroves are clusters of diverse trees and shrubs that grow in coastal intertidal zone. It stabilises the coastlines and protects the land from the powerful wave action and intense storms. The effectiveness of mangroves as natural coastal protection buffer has been well proven in the 2004 Indian Ocean Tsunami that brought devastating economic and ecological impacts to many countries, including Malaysia. Mangroves has been reported to be degraded at an alarming annual rate due to the impacts of natural processes and anthropogenic influences. Many efforts of mangrove restoration have been implemented along the Malaysian coastlines in the past decade, but very few ever survive under the harsh marine environment.